The Effect of Trade Balance on Economic Growth of Somalia (1980 - 2020) - Ahmed Abdulle, Abdulkhaliq (International Journal of Scientific Research and Management (IJSRM), 2022)
The Prime aim of the study was to investigate the relationship between the trade balance and Economic growth of Somalia during the period between 1980 and 2020. The study employed secondary time series data obtained from the World Bank, World Development Indicators (WDI), and African Development Bank. An augmented Dickey-Fuller test (ADF) was adopted in the study to test the Stationarity of data variables in the study. the Econometric model that was employed in the study was Autoregressive Distributed Lag (ARDL) which aims to find out the short-run and long-run relationships between the dependent variable (RGDP) and independent variable (trade balance). The study revealed that the trade balance (TB) has a significant negative relationship with the real gross domestic product (RGDP) of Somalia in both the Short-run and long run. Furthermore, the Unemployment rate have a significant negative relationship with the gross domestic product (GDP) of Somalia in both the short-run and long run. However, the foreign direct investment (FDI) and gross domestic product (GDP) had a significant negative relationship in the long run while there have an insignificant relationship between them in the short-run. The study recommends that the government of Somalia should improve the countries trade balance by increasing the production, productivity, and export of the country.